Gaps in nutritional research among older adults with cancer - Presley, Carolyn J.; Dotan, Efrat; Soto-Perez-de-Celis, Enrique; Jatoi, Aminah; Mohile, Supriya G.; Won, Elizabeth; Alibhai, Shabbir; Kilari, Deepak; Harrison, Robert; Klepin, Heidi D.; Wildes, Tanya M.; Mustian, Karen; et al. (Journal of geriatric oncology, 2016)
Nutritional issues among older adults with cancer are an understudied area of research despite significant prognostic implications for treatment side effects, cancer-specific mortality, and overall survival. In May of 2015, the National Cancer Institute and the National Institute on Aging co-sponsored a conference focused on future directions in geriatric oncology research. Nutritional research among older adults with cancer was highlighted as a major area of concern as most nutritional cancer research has been conducted among younger adults, with limited evidence to guide the care of nutritional issues among older adults with cancer. Cancer diagnoses among older adults are increasing, and the care of the older adult with cancer is complicated due to multimorbidity, heterogeneous functional status, polypharmacy, deficits in cognitive and mental health, and several other non-cancer factors. Due to this complexity, nutritional needs are dynamic, multifaceted, and dependent on the clinical scenario. This manuscript outlines the proceedings of this conference including knowledge gaps and recommendations for future nutritional research among older adults with cancer. Three common clinical scenarios encountered by oncologists include (1) weight loss during anti-cancer therapy, (2) malnutrition during advanced disease, and (3) obesity during survivorship. In this manuscript, we provide a brief overview of relevant cancer literature within these three areas, knowledge gaps that exist, and recommendations for future research.